Elaboración de un plan de trabajo para el procedimiento de movilización del RIG 50, en el área de Barrancabermeja en el campo la Cira-Infantas (2018)
To the develop of this work, its necessary to identify and recognize the process, steps and stages that should be done in all mobilizations, beginning for the mobilization plan and finalizing with the operative of the equipment. The knowledge of those activities it’s a fundamental part to do the analysis of the historic mobilizations of the Rig 50 in Campo La Cira – Infantas, where deviations that make a long time and expensive mobilization can be classify. Later, being in a mobilization, key opportunities has been seen, this key opportunities pretend improve the mobilization times and decrease the hazards and the costs that are involved at the move of the Rig 50. It's here where the meticulous analysis and the project management software helps to demonstrate activities that demand a high use of resources together with high operative times. Part of this high times were being given by the return and suction tanks. As a method of solution to these delays, an alternative was proposed, which was the mud tanks of the Rig 50 would be replaced by ones with Fast Move characteristics.